Impact assessment of climate change on the future conjunctive water use - DALAI, A; JENA, S K (The Indian Journal of Agricultural Sciences, 2025)
The present study was carried out during rainy (kharif) and winter (rabi) seasons of 2019–20 and 2020–21 in the Puri main canal system’s Phulnakhara distributary command, particularly in the coastal districts of Odisha, in eastern part of India. The study offers a new perspective involving the future climate data driven model resulting water requirement at RCP 4.5 in a canal command and after integrating it with the optimal cropping area, the optimal future irrigation water need for kharif and rabi seasons, have been found out. The impact of climate change was assessed by means of the irrigation water need in future both from the conjunctive use of water sources (surface and groundwater) in the study command area. Based on the prediction results it has been calculated that future irrigation water demand would be the highest in the year 2042–43 during kharif season and in the year 2044–45 during the rabi season, respectively. It was estimated that the decline in groundwater table in kharif would be 1.23–1.42 m below ground level (BGL) and the decline in groundwater table in rabi season would be 1.46 to 1.64 m BGL during the upcoming 30 years (2021–22 to 2050–51). So, the values of groundwater table declination would be the highest in 2042–43 and 2044–45 years for kharif and rabi seasons, respectively. Based on this study, integrating the optimal crop area with future irrigation water need, resulted the groundwater table fluctuation in the permissible limit.